Dynamic Properties Comparison of 1D, 2D, and 3D Model for Concrete Box-Girder Bridge of 40-meter Span - Wira Sucitra Ibrahim; Akhmad Aminullah; Ali Awaludin; Bambang Suhendro; Bambang Supriyadi; Renga Rao Krishnamoorthy (Journal of the Civil Engineering Forum, 2022)
Concrete box-girder structure is considered the thin-walled structure, undergoing deformation and forces, as well as having structural rigidity in three dimensional directions. However, it’s commonly modeled as 1D structure for the sake of design practicality, which influences the numerical result of its dynamic properties when compared to both real time SHMS and field test result. To see how far the difference of the dynamic properties between 1D, 2D, and 3D model of concrete box-girder structure, the concrete box-girder structure is modeled as 1D (frame), 2D (shell), and 3D (solid) element with MIDAS Civil 2019. Considering the allowable deflection and stress limited by design code, concrete box-girder structure is modeled and analyzed as linearly elastic material. The dynamic properties obtained from these 3 models were compared with those obtained from real time SHMS and field test. These results indicate that both natural frequency and period of 2D and 3D models are close to those of real time SHMS and field test. However, the natural frequency of 1D model is slightly larger than the real SHMS and field test, indicating that 1D model gives the slightly overestimate natural frequency and structural rigidity compared to the reality. Unlike 2D and 3D model, the structure is accounted to have the uniform sectional rigidity along transversal direction in 1D model. This is why 1D model seems to have higher structural rigidity compared to 2D and 3D model, which subsequently yields the higher natural frequency than 2D and 3D model. This research proves that the designers’ discretion is advised if 1D model is used for the sake of design practicality.